Pakistan insights 2021-22 : a granular look at key issues in Pakistan - Devasher, Tilak (New Delhi Pentagon press, 2022)
Pakistan Insights 2021-22 takes a granular look at some of the critical issues facing Pakistan. The book begins with a look at the recent developments in Pakistan including the ousting of Prime Minister Imran Khan through a no-confidence motion and the challenges before the new Shehbaz Sharif-led government
Keywords: Author as an IAS; Indian Administration Services; Diplomatic relations